An empirical stock-flow consistent macroeconomic model for Denmark - Mikael Randrup Byrialsen; Hamid Raza (Levy Economics Institute of Bard College, 2020)
This paper emphasizes the need for understanding the interdependencies between the real and financial sides of the economy in macroeconomic models. While the real side of the economy is generally well explained in macroeconomic models, the financial side and its interaction with the real economy remains poorly understood. This paper makes an attempt to model the interdependencies between the real and financial sides of the economy in Denmark while adopting a stock-flow consistent approach. The model is estimated using Danish data for the period 1995-2016. The model is simulated to create a baseline scenario for the period 2017-30, against which the effects of two standard shocks (fiscal shocks and interest rate shocks) are analyzed. Overall, our model is able to replicate the stylized facts, as will be discussed. While the model structure is fairly simple due to different constraints, the use of the stock-flow approach makes it possible to explain several transmission mechanisms through which real economic behavior can affect the balance sheets, and at the same time capture the feedback effects from the balance sheets to the real economy. Finally, we discuss certain limitations of our model.
Keywords: E17; E12; F41; 330; Empirical Stock-Flow Consistent Models; Denmark; Open Economy